A Comparative Thematic Analysis of Political Slogans of PTI and PML-N - Anwar, Nazia; Malik, Moazzam Ali; Butt, Isha Razzaq (Pakistan Languages and Humanities Review, 2024)
The objectives of the present research is to determine and contrast the prevailing themes represented by the PTI and PML-N political slogans as well as investigate the ways in which the slogans indicate the ideological position of the parties. Political slogans are some of the most effective linguistic devices that can summarize the ideology, leadership and emotional appeal using few words. Slogans are used by parties such as PTI and PML-N in Pakistan to create opposing political visions and mobilize the voter base. A qualitative thematic analysis has been adopted for the current research which involved twenty slogans by both parties. These slogans were analyzed by using the critical discourse analysis (Fairclough, 2013) as theoretical framework. Findings of the study reveal that the slogans of PTI focus on reform, justice and transformation, whereas the service, loyalty and democratic legitimacy are the focus of PML-N. Such thematic oppositions demonstrate distorted populist leanings. The research concludes that ideological constructions through discursive tools of political slogans are effective in Pakistan, where the former impacts collective identities and political imagination. The study recommends to study these slogans academically to understand the rhetorical strategies used by political parties in Pakistan. It also acclaims to use a larger data to analyze the political implications of political slogans along with cultural and social variations at global level.